Development of Open Ended Based Mathematics Teaching Materials on Grade X Quadratic Equations and Functions to Facilitate Mathematics Learning Outcomes - Sumarni; Nur, Fitriani; Abrar, Andi Ika Prasasti; Mattoliang, Lisnasari Andi; Majid, Ahmad Farham (Alauddin Journal of Mathematics Education, 2024)
The purpose of this study was to identify the process of developing teaching materials (modules) as well as the degree of validity, practicality, and effectiveness of teaching materials (modules) based on open-ended on equations and quadratic functions of class X at SMAN 8 Bone. This research is classified as development research (Research and Development) and follows the 4D development approach (Define, Design, Develop, and Disseminate). The validation sheet, teacher and student response questionnaire, student activity observation sheet, teacher ability to manage learning observation sheet, and learning outcome test were used in this study. The process of making teaching materials (modules) is divided into four stages, namely the definition stage, design stage, development stage, and distribution stage. Data were collected from product trials to determine whether the product met the criteria of a good product or not. After assessment and development, the quality of the teaching materials (modules) produced is considered very valid with an average validator answer of 4.4. While the teacher response questionnaire shows the practicality of teaching materials (modules) with an average of 92.5% and the competence of instructors to manage learning with an average of 3.8 in the good category. The questionnaire can also be used to assess the effectiveness of teaching materials (modules). The positive student response was 83%, student activity was 81% with a very good category, and the results of the analysis of the learning outcomes test obtained a percentage of student learning completeness of 90.3% and a percentage of completeness of 90.3%. 9,7%. The results of these measurements indicate that the teaching materials have met the standards, so they can be used.